Dung beetle fauna from Mount Mabu. Part 2: Pedaria ricardogutai (Coleoptera: Scarabaeidae), a new species, with an annotated checklist of species of Pedaria Laporte, 1832 from Mozambique - Daniel, Gimo M.; Strümpher, Werner P.; Josso, Jean-François (Zootaxa, 2023)
Mabu Forest in northern-central Mozambique harbours the largest continuous block of rainforest remaining in southern Africa. Also, the region is known for its exceptional levels of biodiversity, including a high level of endemism. Several new taxa of plants and animals have been discovered from previous biological expeditions. Last year, we conducted the first dung beetle exploration in the region—where almost half of the dung beetle species collected are new to science. In this paper, we describe, diagnose and illustrate Pedaria ricardogutai Daniel, Strümpher & Josso, new species. We compared the new species to the most morphologically similar species, Pedaria sudrei Josso & Prévost, 2003. We also provide an annotated checklist of 17 species of Pedaria Laporte, 1832, recorded from Mozambique, including type localities and distribution records.